The effect of sovereign wealth funds on the credit risk of their portfolio companies - Bertoni, Fabio; Lugo, Stefano (Journal of Corporate Finance, 2014)
We study how sovereign wealth fund (SWF) investments affect the credit risk of target companies as measured by the change in their credit default swap (CDS) spreads around the investment announcement. We find that the CDS spread of target companies decreases, on average, following an SWF investment. The reduction in the CDS spread is higher when the SWF is established by a politically stable non-democratic country that has a neutral political relationship with the host country of the target company. Our results suggest that creditors expect SWFs to protect target companies from bankruptcy when it is in the interest of their home country to build political goodwill in the host country of the company.